Bicycling campaigns promoting health versus campaigns promoting safety: A randomized controlled online study of 'dangerization'. Issue 3 (September 2015) - Gamble, Tim; Walker, Ian; Laketa, Aleksandra
Abstract This study tested the idea that promoting bicycle safety might inadvertently discourage bicycling by having negative effects on how the activity is perceived. It also tested the idea that stressing the health benefits of bicycling would have a positive effect on perceptions and intentions to cycle. Two-hundred and twenty-eight adults were randomly allocated to read safety-focused, health-focused, or control publicity materials and their immediate influences on bicycling perceptions were measured. Health-focused materials significantly increased bicycling׳s perceived health benefits amongst non-bicyclists and had no influence on perceived risk; the safety-focused campaign had no effect on either perceived risks or health benefits for either group. Neither campaign measurably changed intentions to bicycle nor the perceived enjoyment of bicycling, both of which were clearly higher amongst bicyclists than non-bicyclists. The study suggests that safety-focused campaigns are unlikely to have any immediate effect on people׳s perceptions and intentions to cycle, whether positive or negative; health-focused campaigns, on the other hand, make bicycling appear more beneficial to those who do not currently do it. In addition, although the possibility exists that current bicyclists are a qualitatively different sub-population, able to enjoy bicycling in non-conducive environments, their rating bicycling as more enjoyable than non-bicyclists hints that new campaigns might usefully emphasise the enjoyment of bicycling to encourage its uptake.